Physical Chemistry from Ostwald to Pauling - The Making of a Science in America. - Servos, John W. (ACLS Humanities E-Book., 1996)
John Servos explains the emergence of physical chemistry in America by presenting a series of lively portraits of such pivotal figures as Wilhelm Ostwald, A.A. Noyes, G.N. Lewis, and Linus Pauling, and of key institutions, including MIT, the University of California at Berkeley, and Caltech. In the early twentieth century, physical chemistry was a new hybrid science, the molecular biology of its time. The names of its progenitors were familiar to everyone who was scientifically literate; studies of aqueous solutions and of chemical thermodynamics had transformed scientific knowledge of chemical affinity. By exploring the relationship of the discipline to industry and to other sciences, and by tracing the research of its leading American practitioners, Servos shows how physical chemistry was eclipsed by its own offspring--specialties like quantum chemistry.